World education patterns in the global South the ebb of global forces and the flow of contextual imperatives - Wolhuter, Charl; Wiseman, Alexander W. 1968- (Emerald Publishing, 2022)
"Comparative and International Education is a dynamic and growing field facing extraordinary challenges in every corner of the world. World Education Patterns in the Global South surveys the educational responses and new educational landscapes being developed as a consequence of the powerful global forces that are demanding change within the Global South’s educational contexts, including Central and South-East Asia, Latin America, and the Caribbean,.These forces include urbanisation in the Global South, the rise of the informal economic sector in the Global South, the changing presence of religion, the Creed of Human Rights, democratisation, and the rise of supranational and international political structures on the one hand and, on the other, sub-national and decentralised structures." -- Page 4 de la couverture
Comprend des résumés
Keywords: Comparative education; Éducation comparée